Analisis Kemampuan Penalaran Matematis Dalam Menyelesaikan Soal Numerasi Siswa Kelas V SD - Lita Nala Karimah; Dwi Nor Halisa; Luqyana Nasywa Salma; Diana Ermawati (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the numeracy abilities of class V students at SDN 1 Tanjungkarang. This research used descriptive qualitative research methods, data was collected through interviews, observation and documentation from 3 students with low, medium and high numeracy abilities. The results show that 22% of students have low ability, 67% medium, and 11% high. Students with low and medium abilities experience difficulties, especially in division operations, while students with high abilities are better able to overcome problems but still require a deep understanding of the concept. In conclusion, the majority of students indicated that they had not fully mastered numeracy questions. Students with low and moderate abilities tend to experience difficulties in understanding and solving problems, especially in division operations.